Peran Human Capital Dalam Meningkatkan Kinerja Perusahaan - Vip Paramarta; Devi Delvita; Refliza Yanti; Didik Udayana; Amelia Suci Pertiwi; Aep Saepudin (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
This paper provides a literature review that focuses on the relationship between human capital and performance essentially at the firm level. Measurement of human capital is not intended to determine the intrinsic value of HR, but rather the impact of HR behavior on organizational processes. This measurement is important to determine the effectiveness of the company's strategy on how much the employee contributes to improving performance in an increasingly advanced business environment. says there are two main strengths why human capital measurement is the main center of attention in the business community. First, competition in the business environment is a result of the globalization of trade and the development of several key sectors such as telecommunications, transportation and financial services. Second, the rapid development of information technology, especially after the emergence of the internet. These two developments have dramatically changed the business structure and pushed intangible assets to play an increasingly important role for companies.